ANALISIS PENILAIAN PERSEDIAAN UNTUK MENCAPAI LABA OPTIMAL PADA PT. TITIAN GAS - Muhammad Maulana, Lusia Ramanita Eka Yudhyani (EKONOMIA, 2021)
The purpose of this study is to determine the inventory valuation calculation using the FIFO method, to determine the inventory valuation calculation using the Weighted Average method and to find out which method produces a more optimal profit using the FIFO method or the Weighted Average method.The theoretical basis used in this research is cost accounting which focuses on the calculation of LPG inventory valuation at PT. Titian Gas. The hypothesis of this research is that inventory valuation using the FIFO method will produce the more optimal profit than using the Weighted Average method at PT. Titian Gas.          The results showed that the cost of goods sold for 5.5 kg, 12 kg and 50 kg LPG was having a difference where the calculation using the FIFO method obtained a lower total cost of goods sold than using the Weighted Average method so that the gross profit using the FIFO method could be generate higher profits than using the Weighted Average method.            The conclusion from this research is that the calculation of inventory valuation using the FIFO method produces a more optimal profit than using the Weighted Average method